Late Occurring Medial Migration of a Lag Screw in Gamma Nailing - S. van Hoef; M. C. H. W. Fuchs; R. H. M. ten Broeke (Case Reports in Orthopedics)
An 81-year-old female was treated for a pertrochanteric multifragmentary fracture of the proximal femur with a third-generation Gamma nail. After 3 months she presented herself again with acute pain and inability to bear weight on the leg. Radiographs showed medial migration of the lag screw. She was treated with a total hip arthroplasty, after which she was successfully discharged. In this case report the possible causes of this late and unusual complication are discussed.